STUDI DENDROLGIS JENIS-JENIS POHON DI AREAL KAMPUS POLITEKNIK PERTANIAN NEGERI KUPANG - Ni Kade A. D. Aryani; Yudhistira A. N. R. Ora; Fransiskus X. Dako; . Adrin (Politeknik Pertanian Negeri Kupang, 2008)
Study Dendrology of Trees Spesies in Kupang State Agricultural Polytechnic. The research was conducted on field of Politani Kupang, in order to identify trees species located in Politeknik Pertanian Negeri Kupang area. The research used Census method to collected materials on the field; Descriptive method to obtained special characteristics of plants, was held on the field and laboratory, and Identification to got trees name by compared the tree with its proponent literatures. The result showed that there were 36 species of trees from 14 families growing in Politeknik Pertanian Negeri Kupang. Those were Alstonia scholaris (L.) R.Br.u, Bombax ceiba Linn, Ceiba pentandra (L.) Gaertn., Delonix regia (Hook.) Raf., Cassia siamea Lamk., Casuarina equisetifolia Blanco, Terminalia, Macaranga tanarius Muell. Arg., Caesalpinia pulcherrima Sw., Acacia auriculiformis A. Cunn. Ex Bth., Acacia mangium Wiilld., Pterocarpus indicus Willd., Cassia fistula Linn., Pongamia pinnata Merr., Erythrina subumbrans Merr. Acacia famesiana Willd., Bauhinia monandra Kurz., Albizzia lebbek (L.) Benth., Dialium indum L., Paraserianthes falcataria (L.) Nielsen jeunjing ), Adenanthera pavonina L., Gliricidia sepium (Jacq.) Steud., , Melia azedarach L.,Swietenia macrophylla King., Ficus benyamina L., Melaleuca leucadendron Linn., Santalum album L., Schleichera oleosa Merr., Filicium decipiens (Wight & Arn.) Keywords: trees, vegetation, identification.